An integrated microring circuit design for optoelectronic transformer applications - J. Ali (Results in Physics, 2018)
The on-chip scale circuit of the optoelectronic transformer is designed and manipulated using the microring resonator system. By using the monochromatic input light source, the electro-optic signals can be generated and functioned as the step up and down conversion by mean of the on-chip optoelectronic transformer. The step up and down of the electro-optic related power conversions can be obtained via the input and drop port connections. The results obtained have shown that the flexible up and down electro-optic conversion ratios of 1: 5 and 10:1 for the step up and down conversions, respectively. The uses light source wavelength source was centered at 800 nm, where the conversion stability of 1600 fs is noted. The linearity trend of the conversion stability is confirmed.